The Capability of Canna edulis Ker Starch as Carboxymethyl Cellulose Replacement on Yogurt Drink During Cold Storage - Umam, Ahmad Khoirul; Lin, Mei Jen; Radiati, Lilik Eka; Peng, Shao Yu (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2018)
The decreasing of yogurt drink quality will occur during storage. Stabilizer that usually used for maintaining the yogurt quality is a chemical compound namely carboxymethyl cellulose (CMC). Canna (Canna edulis Ker) potentially used as a natural stabilizer, which is a local Indonesian tuber with high starch content and antioxidative properties. The purpose of this study is to investigate the capability of Canna starch to replace the used of CMC based on the physicochemical and antioxidant activity of yogurt drink during cold storage. The complete randomized factorial design will be used with two factor. The first factor was Canna starch/CMC levels divided into 5 groups, T0 (0.2%CMC) as a control, T1 (0.15% CMC + 0.025% canna), T2 (0.1% CMC + 0.05% canna), T3 (0.05% CMC + 0.075% canna), and T4 (0.1% Canna), respectively. The second factor was the storage time of yogurt drink divided into four groups, 1, 7, 14 and 21 days, to determine the quality change during stored in the refrigerator at 4Â°C. Data obtained from the results of subsequent studies analyzed by GLM (General Linear Model) and followed by Duncan's multiple range test (DMRT). This study resulted that Canna starch has the capability as a natural stabilizer for producing functional yogurt drink with potential health benefits related to the high antioxidant activity. The combination of 0.1% CMC and 0.05% Canna starch addition on yogurt drink manufacture showed the best physicochemical quality